If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 4x = 27 Reorder the terms: 4x + -3y = 27 Solving 4x + -3y = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 4x + -3y + 3y = 27 + 3y Combine like terms: -3y + 3y = 0 4x + 0 = 27 + 3y 4x = 27 + 3y Divide each side by '4'. x = 6.75 + 0.75y Simplifying x = 6.75 + 0.75y
| 4(2x+4)+5(3x-5)= | | 12(3x+5)-(2+3x)7=346 | | 6x+-5y=16fory | | 4-x(-2)= | | -8n-7+3=15 | | 8+2v=4 | | 13x-3=-11 | | b//8=-3 | | 21=-1.5x | | 112+12m=208 | | 2y+3-y-(-2)= | | 3x-8y=100 | | -2+4=4-3 | | 34=-9+7(b-2) | | 20n-16=304 | | 7(2x+4)=6(2x-3) | | 11w=5940 | | 34=9+7b-14 | | 5(-6)+14x=22x-(-6) | | 5y=2y+g | | 8x(x+7)=5x+35 | | 30-4-7=m | | mg=5 | | 3/10-3/5= | | Tan(55)*20=x | | 225-8y=17 | | -2(3x-4)=4x-10-x | | 1.5x(x-2)+9=1.5x+6 | | 7x^3-x^2+14x+7xy=0 | | 3.4x=-0.238 | | lny=ln(9x)+c | | .3333x=8 |